A decade of age-related macular degeneration risk models: What have we learned from them and where are we going?. (4th July 2017) - Zhang, Michael; Baird, Paul N.
ABSTRACT: The genomic revolution has revealed the complexity of multifactorial diseases, making the development of effective diagnostics extremely challenging. In turn, the prospect of precision medicine as applied through targeted therapeutic treatments continues to remain largely elusive. Age-related macular degeneration (AMD) as a complex disease falls under this category, despite it being one of the most well characterized multifactorial diseases. This reflects both the extent of identified genetic components and known environmental risk factors. Additional considerations in dissecting out the roles played by genetic and non-genetic risk factors arise through the rapid increase in prevalence of AMD with age and the varying time periods over which disease progression can occur, complicating efforts to discriminate between "progressors" and non-"progressors." As a consequence, extensive research into the aetiology of AMD is yet to realize a clinically acceptable predictive test. This review covers the current climate of risk models in late AMD but will focus mainly on genetic risk factors as well as the types of models that have currently been employed in the AMD modelling literature.